The Effects of Job Design on Turnover, Absenteeism and Health - Mikalachki, A. (Relations industrielles / Industrial Relations, 1975)
The purpose of this article is to show how the deleterious consequences of personnel turnover, absenteeism, and occupational illness are related to job designs which are inappropriate to the needs of workers.